2019
DOI: 10.1111/resp.13696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of E‐cigarette E‐liquid components on bronchial epithelial cells: Demonstration of dysfunctional efferocytosis

Abstract: Background and objective: E-cigarettes are often marketed and thought of as emitting harmless vapour; however, verification of their safety for non-smokers is scarce. We have previously shown that E-cigarettes cause decreased phagocytosis of bacteria by macrophages via reductions in surface bacterial recognition receptors. This study assessed the effect of E-cigarette constituents, 3 E-liquid apple flavours, nicotine, vegetable glycerine and propylene glycol, on bronchial epithelial cell viability, apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 67 publications
(159 reference statements)
0
20
0
1
Order By: Relevance
“…Several physiologic mechanisms, including lung surfactants, mucociliary clearance, and phagocytosis of the inhaled particulates, are paramount in maintaining the airway homeostasis. The airway epithelial cells (AECs), including alveolar type I (AT-I) and type II (AT-II) cells, alveolar macrophages (AMs), and the granulocytes or polymorphonuclear cells (PMNs) are the prominent airway innate immune cells driving these physiological functions and are among the first responders following the ENDS aerosol/vape exposure, as depicted in Figure 1 AMs are the resident professional phagocytes that ingest and degrade different inhaled irritants, pathogens, and apoptotic cells by ''efferocytosis'' to help reduce inflammatory responses in the damaged tissues (Ween et al, 2019). Exposure to ENDS and vaping products changes the phenotype and function of AMs and suppresses their efferocytotic activity that helps clear the insult.…”
Section: Disussion On Cellular and Molecular Mechanisms Of Evalimentioning
confidence: 99%
“…Several physiologic mechanisms, including lung surfactants, mucociliary clearance, and phagocytosis of the inhaled particulates, are paramount in maintaining the airway homeostasis. The airway epithelial cells (AECs), including alveolar type I (AT-I) and type II (AT-II) cells, alveolar macrophages (AMs), and the granulocytes or polymorphonuclear cells (PMNs) are the prominent airway innate immune cells driving these physiological functions and are among the first responders following the ENDS aerosol/vape exposure, as depicted in Figure 1 AMs are the resident professional phagocytes that ingest and degrade different inhaled irritants, pathogens, and apoptotic cells by ''efferocytosis'' to help reduce inflammatory responses in the damaged tissues (Ween et al, 2019). Exposure to ENDS and vaping products changes the phenotype and function of AMs and suppresses their efferocytotic activity that helps clear the insult.…”
Section: Disussion On Cellular and Molecular Mechanisms Of Evalimentioning
confidence: 99%
“…The comprehensive harmful effect of EC constituents, including E-liquid flavors, nicotine, VG and PG, has been also investigated by Ween et al, showing increased bronchial epithelial apoptosis and macrophage efferocytosis dysfunction in bronchial epithelial cells. Interestingly, the authors found that EC can alter bronchial epithelial cell cytokine secretion pathways in a flavor-dependent manner (45). In a more recent study, the flavoring profile of E-liquids has been found to cause bronchial epithelial cell apoptosis, alveolar macrophage phagocytic dysfunction, and to alter airway cytokines, pointing out the issue of regulating flavored E-liquids and the need of more rigorous studies providing clear data on the health impacts of flavored ECs (46).…”
Section: Staudt Et Al (50)mentioning
confidence: 99%
“…However, since 2017 prestigious professional bodies: the American Heart Association, the Australian Lung Foundation and the European Respiratory Society have seemed to be more conservative and announced reservation for the widespread and unregulated use of vaping 16–18. In September 2019, an in vitro study demonstrated decreased Tumor Necrosis factor α (TNF-α) production in lung epithelium cell culture; however, its clinical relevance is yet unknown 19…”
Section: Safety Of Vaping Nicotine-containing Liquidsmentioning
confidence: 99%